The Outcomes of Patients Incidentally Confirmed with Covid-19 After Cardiac Surgery - Uysal, Ayhan; Erturk, Esra; Abacilar, Ahmet Feyzi; Duman, Umit; Dogan, Omer Faruk (Imr Press, 2021)
Background: The aim of this study was to investigate the clinical outcomes of cardiac surgery in patients who were incidentally diagnosed with Covid-19 in the postoperative period. Patients and methods: We performed 826 open cardiac surgeries in five tertiary centers. Most of the surgeries were elective coronary artery bypass grafting (CABG) (93.8%). A preoperative RT-PCR test and transcutaneous oxygen saturation were routinely investigated prior to surgery. We also investigated whether the patients already received Covid-19 treatment or had any contact with a Covid-19 patient in the last two weeks. We analyzed high sensitive C-reactive protein (hs-CRP), d-dimer, and fibrinogen, which plays a main role in the activation of procoagulant state after surgeries. Results: Acute lung injury related to Covid-19 activation was observed in 48 out of 826 patients (5.8%). The median age of 48 patients was 63.9 +/- 12.4 years. Euro-Score and body mass index (BMI) were 6.1 +/- 1.1 and 29.2 +/- 4.1kg/m(2), respectively. RT-PCR test results were positive in 29 patients (60.4%). We performed thoracic computed tomography (CT) in all patients with or without positive RT-PCR test results. Thoracic CT images showed that there was a different degree of ARDS (mild, moderate, and serious). The median time of extracorporeal circulation (ECC) was 93.2 +/- 14.6 min. in on-pump surgery (IQR, 68-155 min.). Common symptoms included dyspnea (N. 22; 45.8%) and fever (N= 12; 25%). Eleven patients needed readmission to ICU. Compared with non-admitted to ICU patients, ICU patients were higher comorbidities and severe laboratory abnormalities (eg, high blood d-dimer and fibrinogen). We also detected significantly low oxygen saturation, hypercapnia, and severe acidosis in readmitted patients. Radiologic investigations showed that there were severe ARDS with bilateral pneumonic infiltration resistant to medical treatment in 6 out of 11 patients who died (54.5%). Conclusion: Diffuse pneumonic infiltration related to Covid-19 may develop in asymptomatic cardiac surgery patients with negative RT-PCR test results. Immunologic disorders resulting from ECC, physiologic distress, and anesthesia may activate Covid-19 during incubation period. We need randomized clinical trials to explain Covid-19 activation in latent period of the virus, and clinical outcomes in cardiac surgery.